Surrogate markers for survival in patients with AIDS and AIDS related complex treated with zidovudine. Issue 6768 (12th January 1991) - Jacobson, M. A.; Bacchetti, P.; Kolokathis, A.; Chaisson, R. E.; Szabo, S.; Polsky, B.; Valainis, G. T.; Mildvan, D.; Abrams, D.; Wilber, J.
Abstract : OBJECTIVE–To determine whether early effects of zidovudine treatment on CD4+ lymphocyte count and concentrations of beta 2 microglobulin, neopterin, or HIV p24 antigen or antibody are correlated with survival in patients with AIDS or AIDS related complex. DESIGN–Retrospective study of changes in laboratory markers and survival. SETTING–Multicentre trial at university hospital clinics. SUBJECTS–90 Patients with AIDS or AIDS related complex. INTERVENTION–Patients started zidovudine 200 mg orally every four hours. Fifty six of the patients died a median 17 months after starting zidovudine; the remaining 34 patients were followed up for a median 25.5 months. MAIN OUTCOME MEASURES–Changes in CD4+ lymphocyte count and serum concentrations of p24 antigen and antibody, beta 2 microglobulin, and neopterin; survival of the patient. RESULTS–The pretreatment characteristics that independently predicted poor survival were determined using a multivariate proportional hazards model: a diagnosis of AIDS (v AIDS related complex), age over 45 years, and the logarithm of serum neopterin concentration. When these baseline characteristics were controlled for the logarithm of CD4+ lymphocyte count at weeks 8-12 of treatment (p = 0.007) and an increase in serum beta 2 microglobulin concentration at weeks 8-12 (p = 0.05) also independently correlated with survival. In the 38 patients with a better pretreatment prognosis, 24 month survival estimated by the product-limit method was 88% for those with a good response on both surrogate markers during early treatment compared with only 50% for those with a poor response on either marker. In the 38 with a worse pretreatment prognosis, 24 month survival was estimated to be 49% for those with a good response on both surrogate markers compared with only 18% for those with a poor response on either. CONCLUSION–These data suggest that CD4+ lymphocyte count at 8-12 weeks and, perhaps, change in serum beta 2 microglobulin concentration could be surrogate end points for clinical outcome in trials of antiretroviral drugs for patients with HIV disease.